A large eddy simulation of flow over a circular cylinder with circumferential triangular riblets: Effects of spanwise coverage ratio. (1st November 2022) - Xing, Fengda; Lei, Chengwang
Abstract: Flow over circular cylinders covered with circumferential riblets of triangular shape with spanwise coverage ratios from 0 (bare cylinder) to 1 (fully covered) is investigated by large eddy simulation at three subcritical Reynolds numbers (2000, 3000 and 3900 respectively). The bare cylinder is considered as a reference case and for validation purpose. Detailed flow structures and boundary layer characteristics are described. For the fully covered cylinder, it is found that flows on the two sides of each riblet interact, forming a structure with stronger turbulent fluctuations and leading to a significantly shorter recirculation length compared to the other cases. The turbulent fluctuations are attenuated to various degrees for the partly covered cylinders. Two semicircular-shaped flow zones with distinct spanwise flows are observed around the riblets adjacent to the bare sections. Among the three partly covered cases under consideration (with spanwise coverage ratios of 0.25, 0.5 and 0.75 respectively), the half-covered cylinder has the largest semicircular-shaped flow zones, associated with the lowest turbulence in the flow field. A zigzag flow separation line is observed on all sections covered with riblets. The variations of the flow behaviours result in different characteristics of the hydrodynamic forces acting on the various cylinders. It is revealed that the lift fluctuation is the lowest for the half-covered cylinder and the highest for the fully covered cylinder. An examination of the sectional hydrodynamic forces further reveals that the sectional drag is higher at the riblet tip than that in the valley. Highlights: Spanwise coverage ratio of riblets has significant effects on the vortical structures around the cylinders. The longest recirculation length is observed behind the half-covered cylinder, whereas the shortest recirculation length is observed behind the fully covered cylinder. The half-covered cylinder has the lowest spanwise averaged fluctuating lift among all the cases. A zigzag-shaped flow separation line is observed on the cylinders covered with riblets..